Central-Provincial Relations for Anti-Schistosomiasis Policy in China - Ka-wai FAN (Iranian Journal of Public Health, 2012)
This paper discusses central-local relations for healthcare policy in China from a principal-agent perspective, based on schistosomiasis control. In order to control the disease, the central government produced the Outline of the Mid-Long-Term National Plan for Schistosomiasis Prevention and Control (2004-2015) in 2004. By discussing the implementation of the National Outline at the provincial level, the author uses principal-agent theory to examine conflict and coordination between the central and provincial governments. The documents were collected from the Internet. Although the central and provincial governments all want to eliminate schistosomiasis, allocating funding among them creates conflict and forms an obstacle to achieving the goal.  This paper extensively discusses the topics related to central-provincial relation and schistosomiasis control program. Further case study on a single province may be needed to intensify the discussion from a micro perspective. The conflict between central and provincial relations needs to be resolved in order to implement the national policy.